Endoscope-assisted resection of nonneoplastic space-occupying lesion in oral and maxillofacial areas. Issue 1 (December 2017) - Li, Yanan; Xue, Runqi; Lai, Qingguo; Xu, Bingbing; Yuan, Kuifeng; Tang, Xiaopeng; Ci, Jiangbo; Sun, Shaolong; Zhang, Zhichao
Abstract Endoscope-assisted oral and maxillofacial surgeries have been applied to the resection of tumors with minimal invasion and good cosmetic outcomes. However, with regard to endoscope-assisted resection of nonneoplastic space-occupying lesion (NSOL) in oral and maxillofacial areas which differ from tumors in treatment, there are no systematic reports. Therefore the advantages and limitations of the endoscopy-assisted approach (EAA) in resection of NSOL remain unclear. In this novel study we describe endoscope technique for resection of NSOL in face and submandibular areas and compare the feasibility and effectiveness of EAA with external approach (EA). Eleven patients underwent EAA and 20 patients underwent EA procedures. The perioperative and postoperative outcomes of the patients were evaluated. The resection of NSOL with EAA was completed successfully with a shorter hospitalization duration, less bleeding, a smaller incison and better satisfaction with appearance than with the EA procedure (P <  0.01). Our study showed that endoscope-assisted resection of NSOL is technically safe, feasible and practicable. Good cosmetic results with minimal invasion can be achieved with this new technique and therefore this may be a promising new standard procedure in oral and maxillofacial areas.